Relapsing paradoxical reaction in miliary tuberculosis: a case report and literature review - Mobeireek, Abdullah (Respirol Case Rep, 2020)
Paradoxical reaction (PR) after initiating anti‐tuberculous therapy (ATT) is a well‐recognized immune phenomenon. Less recognized, however, is a pulmonary reaction that is associated with miliary tuberculosis (TB), which can be a source of diagnostic confusion and progress to respiratory failure and acute respiratory distress syndrome (ARDS). We report an elderly patient who developed PR associated with respiratory failure following ATT for miliary TB, with radiological and pathological documentation. He responded to corticosteroids, but relapsed twice when the dose was reduced. It is imperative to be familiar with this form of PR to avoid diagnostic pitfalls and initiate appropriate therapy.